2017
DOI: 10.18632/oncotarget.17705
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of DNA methylation-mediated regulation of long non-coding RNAs in breast cancer

Abstract: Although systematic studies have identified a host of long non-coding RNAs (lncRNAs) which are involved in breast cancer, the knowledge about the methyla-tion-mediated dysregulation of those lncRNAs remains limited. Here, we integrated multi-omics data to analyze the methylated alteration of lncRNAs in breast invasive carcinoma (BRCA). We found that lncRNAs showed diverse methylation patterns on promoter regions in BRCA. LncRNAs were divided into two categories and four subcategories based on their promoter me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 76 publications
0
11
0
Order By: Relevance
“…Recently, epigenetic silencing of tumor-suppressor lncRNA by aberrant DNA hyper-methylation attracts increasing attention in a variety of cancer [ 27 29 ]. To explore the epigenetic mechanism by which lnc- RAB11B-AS1 is regulated in osteosarcoma, we assessed the DNA methylation status of promoter region of lnc- RAB11B-AS1 in six paired osteosarcoma and adjacent normal samples.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, epigenetic silencing of tumor-suppressor lncRNA by aberrant DNA hyper-methylation attracts increasing attention in a variety of cancer [ 27 29 ]. To explore the epigenetic mechanism by which lnc- RAB11B-AS1 is regulated in osteosarcoma, we assessed the DNA methylation status of promoter region of lnc- RAB11B-AS1 in six paired osteosarcoma and adjacent normal samples.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic modifications account for aberrant expression of short ncRNAs [ 30 ], but are also implicated in lncRNA dysregulation. Zhang and colleagues integrated multi-omics data to assess alterations of lncRNA methylation in breast invasive carcinoma, highlighting abnormally methylated lncRNAs involved in several hallmarks of cancers [ 31 ]. In multiple myeloma (MM) cells, the methylation of promoter-associated CpG islands triggered downregulation of KIAA0495, a lncRNA transcribed from chromosome 1p36 [ 32 ]; CpG island hypermethylation also downregulated the KIAA0495/p53-dependent apoptotic modulator PDAM, which in turn established a drug resistant phenotype in glioma cells [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale profiling studies, such as that performed by The Cancer Genome Atlas (TCGA), have revealed thousands of differentially expressed lncRNAs in multiple cancers (12,18), yet little is known of how these candidates function at a molecular level to regulate cellular phenotypes (19). In addition, epigenetic alterations to lncRNA expression have been suggested to contribute to the cancer phenotype (20,21). Only a few lncRNAs have been implicated in LUAD development (22)(23)(24)(25), including H19, ANRIL, MEG3, NEAT1, and MALAT1 (25).…”
Section: Introductionmentioning
confidence: 99%